2023
DOI: 10.3390/jcm12155145
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Outcomes of Faricimab Treatment in Aflibercept-Refractory Eyes with Neovascular Age-Related Macular Degeneration

Abstract: To evaluate the functional and anatomical effects of switching to faricimab for patients with neovascular age-related macular degeneration (nAMD) refractory to intravitreal aflibercept, this retrospective study evaluated patients with nAMD who received intravitreal injections of aflibercept (IVA) every <8 weeks and were switched to faricimab. After switching, the patients were treated with a treatment and extended regimen that started with the interval just before switching and received at least three injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 13 publications
3
8
0
Order By: Relevance
“…Similar reports in Japan have shown success rates of 29.1-40.8%. This is consistent with the prevalence of 32.6% reported in this study [17,18]. The finding that 30% of patients who are refractory to IVA can nearly double their treatment interval at six months is a great hope for patients who receive frequent conventional treatment.…”
Section: Switching Success Ratesupporting
confidence: 91%
See 2 more Smart Citations
“…Similar reports in Japan have shown success rates of 29.1-40.8%. This is consistent with the prevalence of 32.6% reported in this study [17,18]. The finding that 30% of patients who are refractory to IVA can nearly double their treatment interval at six months is a great hope for patients who receive frequent conventional treatment.…”
Section: Switching Success Ratesupporting
confidence: 91%
“…This is the first report to identify the factors associated with the success of switching to faricimab for aflibercept-refractory type 1 MNV. Switching from aflibercept to faricimab for refractory nAMD results in improved visual outcomes and longer dosing intervals in many cases [17,18,[21][22][23]. However, the factors contributing to switch success have not been analyzed owing to the retrospective nature of the studies, short-term follow-up, and relatively small sample size of participants.…”
Section: Factors Affecting Successful Switchingmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the recent papers similarly to our study, report on results with neovascular AMD patients who were switched over to faricimab due to treatment resistance with previous anti-VEGF agents [15-18, 21, 23, 25, 27]. Most of these studies agree that switching over to faricimab proved to be an effective treatment for neovascular AMD for anatomic changes [15-17, 21, 23], with preserved [15,17,23] or improved visual outcomes [18,21], with longer [17,18,25,27] or similar treatment intervals [23] compared to prior anti-VEGF therapy, and is considered safe [16].…”
Section: Discussionsupporting
confidence: 72%
“…Following the pivotal TENAYA and LUCERNE trials [11] and the approval of faricimab in the USA [8] and the European Union [9], several authors reported on their initial experiences with the drug. A handful of real-world studies reported on short-term results [15][16][17][18][19][20][21][22][23][24], but due to the novelty of the drug, studies with 6-months of follow-up [25,26] or longer [27] are only available in a very limited number.…”
Section: Discussionmentioning
confidence: 99%